A routing enhanced localisation algorithm for wireless sensor networks. (20th March 2014) - Zhang, Yuan; Zhou, Jin; Ma, Shuang; Shu, Minglei
Node self–localisation is an essential requirement for most wireless sensor networks (WSNs). Although many localisation algorithms have been developed in literature, the optimisation method is still lacking and leaves much room for further research. In this paper we integrate routing strategy into sensor positioning to propose a more accurate, more stable and faster localisation algorithm called RAAFL. In particular, by setting up a next hop binding table at each sensor node, highly refined transformation routes are formed in the system initialisation step. The optimal path is subsequently adopted in the global position computation step to enhance our previously proposed anchor–free localisation algorithm UAFL. The route discovery process not only supports localisation but also provides a candidate routing protocol for data communication. Simulation results reveal that the performance of RAAFL is optimised in terms of localisation error and localisation time.